Adapting to terrace housing living in Malaysia - Abdul Rahim, Zaiton; Hashim, Ahmad Hariza (Elsevier, 2012)
This paper examines the behavioural and physical adaptation of Malay families living in terrace houses in the urban areas in. The objectives of the study are to examine the behavioural adaptation in relation to Malay culture pertaining to activity system, privacy and social interaction and physical adaptation in the form of terrace housing modification. The study employs a qualitative methodology of case studies involving 11 case studies of Malay families living in the three-bedroom two-storey terrace houses in two urban locations in Malaysia. Findings indicate that behavioural adaptation resulted in changes in some aspects of the culture and housing modifications may provide a more supportive living environment but have adverse effects on individual family and housing community due to the constraints of the existing housing design